Preparation and Characterization of Sansevieria trifasciata Fiber/High-Impact Polypropylene and Sansevieria trifasciata Fiber/Vinyl Ester Biocomposites for Automotive Applications - Apang Djafar Shieddieque; Mardiyati; Rochim Suratman; Bambang Widyanto (International Journal of Technology, 2021)
The increasing demand for vehicles is resulting in environmental problems, such as a higher demand for fossil fuels and higher CO2 emissions. Lightweight materials, such as fiber-reinforced polymers, have been used in automotive components to reduce the weight, fuel consumption, and CO2 emissions of vehicles. Natural fibers are often used as substitutes for glass fibers because they are abundant and require less energy to produce compared to glass fibers. The present research focused on the preparation and characterization of composites reinforced with Sansevieria trifasciata fiber (STF). High-impact polypropylene (HIPP) and vinyl ester (VE) were chosen and compared as matrix materials. The results showed that the mechanical properties of the produced biocomposites increased with increasing amounts of fiber, alkaline treatment, and unidirectional fiber orientation. A tensile strength of 59.77 MPa and a stiffness of 1.97 GPa were obtained for STF/HIPP composites with unidirectional alkali treatment and a 15% volume fraction of fiber. Moreover, a tensile strength of 121.1 MPa and a stiffness of 7.65 GPa were obtained for STF/VE composites with unidirectional alkali treatment and a 15% volume fraction of fiber. The STF/VE biocomposites were comparable to commercial glass fiber composites for automotive applications and even exhibited greater tensile strength properties.